EFEKTIFITAS INTERVENSI DARING UNTUK MENINGKATKAN PENGELOLAAN MARAH PADA SISWA PEREMPUAN - Syifa Salsabila; Efriyani Djuwita (Akademika : Jurnal Teknologi Pendidikan, 2023)
Teenagers experience many emotional problems and tend to be characterized as easily reacting to situations that trigger emotions, including angry emotions. Not all teenagers can apply these skills to be able to display angry emotions in a healthier way. The current study aims to test the effectiveness of online intervention to improve anger management skills in adolescent girls. This research uses a mixed type of research from quasi-experimental methods and qualitative interviews, it aims to test the effectiveness of online interventions to improve anger management in female students. Samples were taken from female teenage students aged 14-16 years who were studying at junior high or high school level. The sampling technique used purposive sampling with four participants who had been screened for difficulties in managing emotions. The instrument used is the Anger Expression Scale (AES). Quantitative analysis using the Friedman test showed that there was a significant difference in students' anger before the intervention, after the intervention, and at follow-up (χ2(2) = 7.600, p = 0.022). There was a significant difference in the anger aspect of students in the three measurement time interval groups (χ2(2) = 6.500, p = 0.039). However, there was no significant difference in the way students expressed anger (2) = 4.500, p = 0.105). There was no significant difference in anger within students (χ2(2) = 0.154, p = 0.926). Thus, it can be concluded that this intervention is not significantly effective in improving anger management skills in adolescent female students.